Evaluating Parent Gym: a community implemented universal parenting programme. Issue 1 (18th March 2019) - Lindsay, Geoff; Totsika, Vaso; Thomas, Ruth
Abstract : Purpose: There is growing evidence of the efficacy and effectiveness of targeted parenting programmes but the evidence for universal parenting programmes is much less developed. The purpose of this paper is to evaluate the effectiveness of Parent Gym, a parenting programme delivered in schools. Design/methodology/approach: In this paper a quasi-experimental design was utilised. Parents were recruited to the Parent Gym programme comprising six two-hour weekly sessions. Parents completed measures of their parenting efficacy, parenting satisfaction, interest in parenting and mental well-being at pre- and post-course. Comparative data were derived from a retrospectively-defined randomly selected group of non-participant parents at two time points, equivalent to the length of the Parent Gym course. Findings: Changes in the Parent Gym group were compared with the comparison group using repeated measures mixed 2×2 ANOVAs, which accounted for the potential effect of demographic characteristics (parent gender, ethnicity, parent age, parent education level and single parent status), and their potential interaction with group membership. Parenting satisfaction showed a significantly greater increase for the Parent Gym group with a large effect size ( d =0.80). Regarding parenting efficacy, there was a significant time × group interaction indicating efficacy scores increased in the Parent Gym group but decreased in the comparison group ( d =1.93). Mental well-being also improved for the Parent Gym group from below the national norm before the course ( d =−0.26) to significantly greater than the national norm at post-course ( d =0.29). Research limitations/implications: A limitation of the present study is the absence of data on outcomes for children. Second, the administration of the research at local level, primarily the distribution and collection of the measures and return to the research team for analysis, is a potential source of data loss: both pre- and post-programme data were available on 55 per cent of Parent Gym parents, similar to other community studies. Third, the present study did not include a longer term follow-up after the programme ended. Future research is required to examine the sustainability of effects produced from community implemented programmes. Practical implications: Findings from the present study indicate that a universal programme, Parent Gym, was effective in aiding the positive development of aspects of parenting behaviour, namely parents' self-efficacy, parenting satisfaction and mental well-being, when delivered in community settings. This demonstrates its potential as part of a regular service delivery option of evidence-based support for parents. Social implications: Successful parenting requires both the development of parenting skills and a positive relationship between parent and child. Parents vary in the resources (e.g. family) available to develop positively. Evidence-based parenting programmes have an important role in aiding parenting development, both those targeted at parents with most challenges and those (universal) aimed across the population. This study demonstrated that the universal Parent Gym programme is effective across a wide range of parents and has the potential to be a positive social resource for community delivery. Originality/value: This is the first rigorous study of Parent Gym. It adds to the limited evidence about parenting programmes delivered outside of trials, as part of normal service delivery. With this evidence, parent choice of a suitable evidence-based programme is increased.